Association between hormonal Imbalance and Interleulin-10 level with Polycystic Ovarian Syndrome of Iraqi women - Al-Quraishy, Hiba Aqeel Muslem; Ali, Hanaa Addai; Al-Tu’ma, Fadhil Jawad; Ali, Mousa Mohsin; Al-Tu’ma, Amir Fadhil (Journal of Contemporary Medical Sciences, 2022)
Objectives: To determine the level of interleukin-10 as inflammatory marker in PCOS patients and compared with healthy control and explore the correlation between IL-10 level and other biochemical markers in PCOS patients. Methods: Whole blood samples of 80 PCOS obese patients and 80 healthy people were collected in duration from Dec., 2021 to April, 2022, at the gynecological and obstetric teaching hospital, Kerbala health directorate, Iraq. The Rotterdam criteria-2003 was accepted to PCOS females with age range between (18-40 years), while the apparently control group with age ranged between (18-40 years). BMI and WHR and hormonal status (LH, FSH, LH/FSH ratio, Prolactin, Free Testosterone) were determined. Elabscience/USA ELISA kit uses the Sandwich-ELISA principle was used to determined IL-10 level in serum. Results: The obese PCOS women had a seriously decrease in IL-10 (pg/ml) level when compare with apparently healthy control group with mean ± SD for patients (2.192 ± 0.47) and for control group (4.532 ± 0.75) P value < 0.0001, and there are significant negative correlations between IL-10 and (BMI p<0.0001, r= -0.66), (WHR p<0.0001, r= -0.66), (LH p<0.0001, r= -0.63), (LH: FSH ratio p<0.0001, r= -0.72), (Prolactin p=0.008, r= -029). Conclusion: Our findings indicate that the IL-10 level decrease in PCOS obese patients and has significant association with pathogenesis and progression of disease.